Dampak Latihan Push Up terhadap Akurasi Shooting Free Throw - Raden Dadan Pra Rudiana; Alda Dwika Damayanti; Arif Fajar Prasetiyo (Mutiara Pendidikan dan Olahraga, 2025)
This study aims to determine the effect of push-up exercise on free throw shooting performance in male students of the basketball extracurricular at SMAN 1 Patokbeusi. The type of research is experimental, with a research design using a “One-Group pretest-posttest design” to observe the impact of the push-up treatment on free throw shooting performance. The population in this study consists of 12 male students from the basketball extracurricular at SMAN 1 Patokbeusi, all of whom were selected as the sample. The instrument used is a free throw shooting test, with a validity of 0.890 and reliability of 0.880. Data analysis was conducted using a t-test at a 5% significance level. The analysis results show “There is an effect of push-up exercise on free throw shooting performance in male students of the basketball extracurricular at SMAN 1 Patokbeusi,” with a t-value of 16.258 > t-table value of 2.201 and a significant value of 0.000 < 0.05.